Analisis Trend Berita Media Online di Masa Pandemi Covid-19 dengan Metode Monte Carlo - Maria Yuhilda Lima; Hustinawati Hustinawati (STMIK Budi Darma, 2023)
The News reports for online media always follows the trending issues that are actually predictable. In general, online media news apart from presenting various events that have occurred, also focuses on reporting issues which is of concern to the public. During the Covid-19 pandemic, almost all mass media, including online media, continued to report various news about the Covid-19 case and its impact on society. The problem is how to understand the news accumulation in a certain period of time to find out the trend in reporting on Covid-19. Because the news has resulted in a huge accumulation of data related to Covid-19 news which can be used to build data mining. The purpose of this study is to analyze online media coverage during the Covid-19 pandemic using the Monte Carlo method to find out news trends. The process uses a data mining approach by collecting a lot of data from existing reports and processing the data to find important information from the data set. The data used to analyze news trends were taken from the main news on the online media Suarapembaruan.com for seven (7) months and processed using knowledge discovery in database (KDD) techniques. The Monte Carlo method is applied to data mining to calculate probability values or possible values that will occur in the future. The results of this study indicate that the trend of news related to Covid-19 in the future will be dominated by News on the Handling of Covid-19 with a trend percentage rate of 23.12 percent. Meanwhile, the news about the Covid-19 Case and the Impact of Covid-19 was getting lower with a trend rate of 21.82 percent and 19.22 percent. Meanwhile, The Other News with related to Covid-19 has a higher trend percentage of 35.84 percent